Assessing cocoa (Theobroma cacao L.) growth under facilitating tree stands of Neolamarckia cadamba and Falcataria moluccana with potential for land restoration - Dumil, Haverdly; Bahrin, Mohammad Azriel; Triscca, Vhienna; M Khatta, Aida Nabihah; Kamlun, Kamlisa Uni; Muda, Boney; Hassan, Affendy; Awang Besar, Normah (Brawijaya University, 2025)
In the field of agroforestry, Theobroma cacao, Neolamarckia cadamba, and Falcataria moluccana are commonly employed to assess growth performance; however, research on their above-ground and below-ground characteristics remains limited. This study aimed to evaluate the growth performance and root distribution of these species within both monocropping and intercropping systems in Madai, Kunak, Sabah, for a six-month period. The study utilised 20 plots arranged in a Randomized Complete Block Design with five treatments: monocropping of T. cacao, N. cadamba, and F. moluccana, as well as intercropping combinations of N. cadamba with T. cacao and F. moluccana with T. cacao. Key metrics measured included height and diameter for above-ground growth, along with Specific Root Length (SRL), Root Length Density (RLD), and Root Biomass (RB) for below-ground growth. The findings indicated that in monocropping, T. cacao achieved an average height of 3.79 m and F. moluccana 5.11 m, while intercropping combinations exhibited various heights. Overall, T. cacao demonstrated robust height and root growth in monocropping systems, with no significant differences observed between above-ground and below-ground parameters.